Failure Analysis and Improvement of Auxiliary Inverter for S8 Line of Nanjing Metro - Yuhu JIANG; Caixia SHI (机车电传动)
Working principle and structure of auxiliary inverters (SIV) for metro vehicles on Nanjing metro line S8 were introduced. The deficiencies in the control of auxiliary inverters for metro vehicles were summarized by analyzing the causes of faults,and relevant optimization measures were put forward. With the test and verification of projects, the problems existing in the auxiliary inverter were solved, which improved the stability of the auxiliary power supply system of the subway train, reduced the operation and maintenance cost.